Alterations in maximal inspiratory mouth pressure during a 400-m maximum effort front-crawl swimming trial - Thomaidis, S. P.; Toubekis, A. G.; Mpousmoukilia, S. S.; Douda, H. T.; Antoniou, P. D.; Tokmakidis, S. P. (The Journal of Sports Medicine and Physical Fitness, 2009)
Aim. The aim of this study was to examine the changes of maximal inspiratory mouth pressure (PImax) during a 400-m front crawl swimming trial. Methods. Eleven well-trained competitive swimmers (age: 17.6±0.8 years, mean±SE) performed a 400-m front-crawl trial with maximum effort (296.2±4.76 s). Then, on different days they swam a 300-m, 200-m and 100-m trials at a velocity corresponding to the 400-m trial. Measurements of PImax from residual volume at upright body position before and immediately after each trial were conducted using a portable mouth pressure meter. Results. Maximal inspiratory mouth pressure did not change significantly after the 100-m and 200-m trial compared to baseline (131.8±9.7 and 123.7±10.3 vs. 140.9±8.9 cmH2O, P>0.05). However, PImax was significantly lower after the 300-m (118.8±7 cmH2O, P=0.02) and 400-m trials (118.1±9.9 cmH2O, P=0.01). Conclusions. These results indicate that during a maximum effort of 400-m front crawl, the reduction of inspiratory muscle strength occurs after 300-m. This should be considered for competitive swimming training by implementing swim race distance-specific respiratory muscle training.